Antebellum Posthuman Race and Materiality in the Mid-Nineteenth Century - Ellis, Cristin (Fordham University Press, 2018)
From the eighteenth-century abolitionist motto Am I Not a Man and a Brother? to the Civil Rights-era declaration I AM a Man, antiracism has engaged in a struggle for the recognition of the humanness of black humanity. It has done so, however, during an era in which the very definition of the human has been called into question by the rising prestige of the biological sciences whose materialist account of human being erodes the grounds of human exceptionalism...Antislavery materialism allowed these authors to respond to scientific racism in its own empirical terms. At the same time, however, it also attenuated their faith in the liberal humanist principles that they champion elsewhere in their work. This antebellum conflict between the liberal ideals of freedom and a materialist ontology of contingency not only presages current critical debates between new materialist and social justice theorists, but reveals an intrinsic tension between posthumanism's embodied ontology and the...